Appraisal on accumulation of nanoenabled agrochemicals in plants with subsequent morphophysiological implications - Kumar P.; Singh K.; Singh A.K.; Singh N.; Singh S.; Rajput V.D.; Minkina T.; Mishra S.K.; Tiwari K.N. (My University, 2025)
The use of agricultural goods that are nanoenabled with nanotechnology, including nanoemulsions, nanoherbicides, nanofertilizers, and nanopesticides, to enhance the efficacy of agrochemical distribution to crop plants has become a more practical option. Many experiments have shown that the use of nanoagrochemicals has the efficacy of lowering the negative effects of chemical-derived fertilizer on the natural environment, in addition to significantly boosting crop yield. Still, new evidence suggests that goods made using nanotechnology not only have the ability to boost agricultural productivity but also bring about changes to the condition of the crop. There have been reports of variations in the amount of carbohydrates, amino acids, and starch present, in addition to the necessary metals. The levels of verbi gratia, albumin, globulin, and prolamin have dramatically increased in rice that has been subjected to CeO2-engineered nanoparticles (ENPs), whereas the levels of calcium, magnesium, and phosphorus have risen in different crops that received treatments treated with CeO2, CuO, and ZnO ENPs. On the other hand, researchers found that Mo and Ni levels dropped in both cucumbers and kidney beans after they were treated with synthetic nanoparticles made of CeO2 and ZnO, respectively. However, brief studies on the particular effects of nanoenabled agrochemical in agricultural area have been disscussed. © 2024 Elsevier Inc. All rights reserved.